«La tengo tratada de casar a esta india...» Condición colonial, poder y sexualidad en la historia de Isabel de Arroyo (Huarmey, 1651) - Arana Bustamante, Luis (2008)
This is a microhistorical study of a documental fragment about a case of amancebamiento in a mid-colonial town in coastal Central Peru. The main concern is to retrieve from judicial testimonies the many dimensions of colonial experience in the social and inter-personal relationships between the protagonists. We follow the case in a form of ‘open’ writing to show the way of principal deductions and the basis and limits of the interpretation offered here.